Effect of sinusoidal-wavy channel of reformer on power of proton exchange membrane fuel cell. (5th November 2019) - Perng, Shiang-Wuu; Wu, Horng-Wen
Graphical abstract: Schematic illustrations of the common and sinusoidal-wavy flow channels. Highlights: A novel sinusoidal-wavy channel improves reforming performance of methanol reformer. Sinusoidal-wavy channel can trap more fuel and force more fuel into catalyst layer. Larger-amplitude and shorter-wavelength enhance hydrogen-yield of a novel reformer. The novel reformer enhances estimated net power of PEM fuel cell up to 29.17%. The novel reformer improves hydrogen yield up to 94%, methanol conversion up to 31.71%. Abstract: The methanol steam reactor (MSR) combined with proton exchange membrane (PEM) fuel cells is regarded as an optimistic miniature power source. The computational fluid dynamics (CFD) simulations are performed to acquire the reforming performance of the MSR with the sinusoidal-wavy channels. The objective of this CFD study is to examine how the wavelength and amplitude of sinusoidal-wavy channel enhance the hydrogen gain and estimated net power of PEM fuel cell under different wall temperatures. The numerical results are also verified by experimental data. The results exhibit that the sinusoidal-wavy channel obviously enhances the reforming performance and the estimated net power of PEM fuel cell since it produces the blockage and trapping effects on the reacting gas to supply more reforming fuel to the catalyst layer and prolong the reacting residence time for enhancing catalytic reaction. In addition, the estimated PEMFC net power and methanol reformation are improved while the wall temperature rises because the higher wall temperature results in the greater catalytic reaction rate.